Antarctic radio frequency albedo and implications for cosmic ray reconstruction. Issue 1 (12th January 2015) - Besson, D. Z.; Stockham, J.; Sullivan, M.; Allison, P.; Beatty, J. J.; Belov, K.; Binns, W. R.; Chen, C.; Chen, P.; Clem, J. M.; Connolly, A.; Dowkontt, P. F.; et al.
Abstract We describe herein a measurement of the Antarctic surface "roughness" performed by the balloon‐borne ANITA (Antarctic Impulsive Transient Antenna) experiment. Originally purposed for cosmic ray astrophysics, the radio frequency (RF) receiver ANITA gondola, from its 38 km altitude vantage point, can scan a disk of snow surface 600 km in radius. The primary purpose of ANITA is to detect RF emissions from cosmic rays incident on Antarctica, such as neutrinos which penetrate through the atmosphere and interact within the ice, resulting in signal directed upward which then refracts at the ice‐air interface and up and out to ANITA, or high‐energy nuclei (most likely irons or protons), which interact in the upper atmosphere (at altitudes below ANITA) and produce a spray of down‐coming RF which reflects off the snow surface and back up to the gondola. The energy of such high‐energy nuclei can be inferred from the observed reflected signal only if the surface reflectivity is known. We describe herein an attempt to quantify the Antarctic surface reflectivity, using the Sun as a constant, unpolarized RF source. We find that the reflectivity of the surface generally follows the expectations from the Fresnel equations, lending support to the use of those equations to give an overall correction factor to calculate cosmic ray energies for all locations in Antarctica. The analysis described below is based on ANITA‐II data. After launching from McMurdo Station in December 2008, ANITA‐II was aloft for a period of 31 days with a typical instantaneous duty cycle exceeding 95%.